Genetic diversity, asymmetrical aggression, and recognition in a widespread invasive species - Tsutsui, Neil D. (The National Academy of Sciences, 2003)
The evolution and persistence of cooperative social units depends on the ability to distinguish group members from nonmembers. The precision of discrimination, in turn, relies on variation in the labels that individuals use to recognize group members. However, this same variation can be selected against if individuals that are rejected as nonmembers incur a high cost. Here we provide evidence that selection against individuals from genetically diverse groups has contributed to the formation of the unicolonial colony structure that characterizes introduced populations of the invasive Argentine ant (Linepithema humile). Studies in both the laboratory and the field showed that individuals from less genetically diverse colonies attack individuals from more diverse colonies and that attackers survived agonistic encounters more than six times as often as recipients of aggression. This selection, in concert with reductions in genetic diversity after a founder event, likely creates a barrier to the establishment of new, genetically diverse introductions from the native range and may reduce genetic diversity within established populations in the introduced range.